Margaret Sanger; rebel with a cause. - Coigney, Virginia (Garden City, N.Y., Doubleday, 1969)
A biography of the woman who campaigned for the social rights of women and especially for the lawful provision of birth control information.
Bibliography: p. [187]
Keywords: Sanger, Margaret, -- 1879-1966.; Sanger, Margaret, -- 1879-1966.; Birth control -- Biography